The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/nar/gku1062
|View full text |Cite
|
Sign up to set email alerts
|

Update on RefSeq microbial genomes resources

Abstract: NCBI RefSeq genome collection http://www.ncbi.nlm.nih.gov/genome represents all three major domains of life: Eukarya, Bacteria and Archaea as well as Viruses. Prokaryotic genome sequences are the most rapidly growing part of the collection. During the year of 2014 more than 10 000 microbial genome assemblies have been publicly released bringing the total number of prokaryotic genomes close to 30 000. We continue to improve the quality and usability of the microbial genome resources by providing easy access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
126
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 15 publications
0
126
0
1
Order By: Relevance
“…A substantial proportion of complete bacterial genomes in the public domain belong to human pathogens and very closely related genomes representing variations within the species (Tatusova et al, 2014). As first reported by Graur, 2014, it has been suggested that this fact might introduce a bias to the bimodal distribution seen in the previous analyses.…”
mentioning
confidence: 87%
“…A substantial proportion of complete bacterial genomes in the public domain belong to human pathogens and very closely related genomes representing variations within the species (Tatusova et al, 2014). As first reported by Graur, 2014, it has been suggested that this fact might introduce a bias to the bimodal distribution seen in the previous analyses.…”
mentioning
confidence: 87%
“…This has led to a rapid increase in the sequencing of whole genomes of microorganisms, including eukarya, bacteria, archaea, and viruses. These sequences have been deposited in the National Center for Biotechnology Information (NCBI) RefSeq genome collection database (http://www.ncbi.nlm.nih.gov/genome) (Tatusova et al, 2015). In 2014, over 10 000 microbial genomes were released (Tatusova et al, 2015).…”
Section: Whole Genome Sequencing Is a Feasible Way To Investigate Thementioning
confidence: 99%
“…These sequences have been deposited in the National Center for Biotechnology Information (NCBI) RefSeq genome collection database (http://www.ncbi.nlm.nih.gov/genome) (Tatusova et al, 2015). In 2014, over 10 000 microbial genomes were released (Tatusova et al, 2015). Along with the next generation platforms, wholegenome analysis of multi-drug resistance mechanisms has emerged.…”
Section: Whole Genome Sequencing Is a Feasible Way To Investigate Thementioning
confidence: 99%
“…All three strains were annotated using the Rapid Annotations using Subsystems Technology (RAST version 2.0) (34) with parameters allowing for frameshift error corrections. The genomes were also annotated using the NCBI Prokaryotic Genome Annotation Pipeline (35).…”
Section: Methodsmentioning
confidence: 99%